2013
DOI: 10.1259/bjr.20101115
|View full text |Cite
|
Sign up to set email alerts
|

Computerised analysis of osteoporotic bone patterns using texture parameters characterising bone architecture

Abstract: Objective: To evaluate the geometric change of osteoporotic bone trabecular patterns using root mean square (RMS) values, first moment power spectrum (FMP) values and fractal dimension values. With the use of these methods, we attempted computerised analysis of osteoporotic bone patterns using texture parameters characterising bone architecture and computer-aided diagnosis of osteoporosis. Methods: 32 patient cases from Korea University Guro Hospital were analysed. Patient ages ranged from 51 to 89 years, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although, for many years, the reference for diagnostic imaging of bone in humans was the interpretation of a radiologist [25], who is a specialist in diagnostic imaging, the ability of the observer to detect image details does not necessarily reflect the amount of information present in the image [24]. Therefore, many attempts have been made to evaluate bone tissue structure, which is especially susceptible to textural analysis [39]. The idea of using textural analysis for the evaluation of human tissue visualized in diagnostic imaging techniques is not new.…”
Section: Discussionmentioning
confidence: 99%
“…Although, for many years, the reference for diagnostic imaging of bone in humans was the interpretation of a radiologist [25], who is a specialist in diagnostic imaging, the ability of the observer to detect image details does not necessarily reflect the amount of information present in the image [24]. Therefore, many attempts have been made to evaluate bone tissue structure, which is especially susceptible to textural analysis [39]. The idea of using textural analysis for the evaluation of human tissue visualized in diagnostic imaging techniques is not new.…”
Section: Discussionmentioning
confidence: 99%
“…As a new technology, radiomics can produce many features that reflect the microstructure of images. Some studies have shown that there is a certain correlation between the texture parameters of cancellous bone extracted from radiological images and bone microstructure [ 19 , 20 ]. He et al have established a radiomics model based on MRI for the diagnosis of osteoporosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Textural features are used to parametrize the spatial patterns of an image responsible for its visual appearance as brightness coarseness, smoothness, and regularity, where most of these appearances are perceived by human senses [17]. Since the implementation of the MR analysis grey-level co-occurrence matrix by Haralick et al [18], magnetic resonance image textures have been used for the analysis of medical imaging in certain cases, such as cerebral tissue [1923], liver [24], breast [19], bone marrow [25], muscle [26], fat tissue [27], bone, the prostate for automated cancer detection [28], and colorectal cancer monitoring [29, 30]. The quality of diffusion tensor imaging (DTI) was also parametrized [31, 32].…”
Section: Introductionmentioning
confidence: 99%